Addition of daratumumab to standard triplet regimens achieved better survival in newly diagnosed multiple myeloma: a systematic review and meta-analysis of randomized controlled trials - Hu, Bin; Wang, Jun; Fang, Dan; Jiang, Ling; Li, Tianqi; Cao, Jinxia (Frontiers in Oncology, 2025)
BackgroundTriplet regimens, such as bortezomib-lenalidomide-dexamethasone (VRd) and bortezomib-melphalan-prednisone (VMP), were standard treatments for newly diagnosed multiple myeloma (NDMM), but they were non-curative for most patients. The incorporation of daratumumab into these regimens, resulting in quadruplet therapies, has shown improved outcomes, though concerns over increased toxicity remain.MethodsIn this systematic review and meta-analysis, we aimed to compare the efficacy and safety of daratumumab-incorporated quadruplet regimens versus traditional triplet regimens in NDMM. A search of PubMed, EMBASE, and the Cochrane Library identified six randomized controlled trials (RCTs) with 3,056 patients. Outcomes included response rates, minimal residual disease (MRD) negativity rate, progression-free survival (PFS), and adverse events.ResultsCompared with triplet regimens, daratumumab-incorporated quadruplet combinations achieved a higher overall survival rate (ORR) (pooled OR = 2.36, 95% CI: 1.56-3.56, P < 0.0001), rate of complete response (CR) or better (pooled OR = 2.35, 95% CI: 1.99-2.77, P < 0.0001), very good partial response (VGPR) or better (pooled OR = 2.58, 95% CI: 1.76-3.79, P < 0.0001) and MRD negativity (pooled OR = 3.55, 95% CI: 2.54-4.96, P < 0.0001). The addition of daratumumab to triplet regimens significantly improved PFS compared with triplet regimens (pooled HR = 0.45, 95% CI: 0.39–0.52, P < 0.0001). Regarding safety, quadruplet regimens were associated with a higher incidence of lymphopenia, upper respiratory tract infection, pyrexia, and pneumonia.ConclusionIncorporating daratumumab into backbone triplet regimens is associated with improved response rates, deeper remission and prolonged PFS with acceptable toxicity profile in patients with NDMM.Systematic review registrationhttps://inplasy.com/inplasy-2024-12-0026/, identifier INPLASY2024120026.